CMOS‐based implantable glucose monitoring device with improved performance and reduced invasiveness. Issue 10 (1st May 2015) - Kawamura, T.; Masuda, K.; Hirai, T.; Ohta, Y.; Motoyama, M.; Takehara, H.; Noda, T.; Sasagawa, K.; Tokuda, T.; Okitsu, T.; Takeuchi, S.; Ohta, J.
Abstract : An implantable glucose monitoring device based on a CMOS line sensor combined with a glucose‐responsive fluorescent hydrogel is developed. An implantable glucose monitoring device with sufficient sensitivity and response time is realised, which is an improvement over the authors' previous proof‐of‐concept device. A reduction of the sensor size made the device diameter injectable with a commercially available 16‐gauge syringe needle. The sensor's performance was confirmed through both in vitro and in vivo experiments.